Draft Annual Plan Tamil Nadu 2006-07 - Planning Commission (Planning Commission, 2006)
The Tenth Plan (2002-07) of the State of Tamil Nadu was formulated within the broad framework and objectives of the National Plan. In keeping with its position as one of the most socially and economically progressive states in the country, the State is committed to the objective of achieving economic growth within a framework of social justice.
Government of Tamil Nadu, State Planning Commission